Reference to a past learning event as a practice of informal formative assessment in L2 classroom interaction. (October 2019) - Can Daşkın, Nilüfer; Hatipoğlu, Çiler
In this study we are concerned with the informal dimension of formative assessment (FA) in an L2 classroom. We examine those instances that are embedded into everyday learning activities and that emerge in and through classroom interaction contingently, continuously and flexibly. Drawing on the methodological underpinnings of Conversation Analysis (CA), we uncover the emergence of instances of reference to a past learning event (RPLE) in L2 classroom interaction and highlights its relevance to informal FA. Data from a corpus of video-recordings of an EFL classroom in a preparatory school at tertiary level are presented. It is seen that RPLEs occur when the teacher contingently extends the main instructional activity to focus on what was presented interactionally earlier. In this way, the teacher seeks evidence of student knowledge and understanding and/or acts on the negative evidence already elicited in order to enhance learning and shape instruction. The analysis of RPLE instances also brings evidence for the relation between learning and assessment together with the tracking of language learning behaviour in subsequent learning events from the perspective of CA-SLA. As a result, this study bridges a gap between language assessment and classroom research by suggesting that teachers' ability to informally assess for formative purposes is an integral part of their classroom interactional competence.